Happiness and morality in Christian moral ethics and in philosophical ethics - Brînzea, Nicolae (Technium Social Sciences Journal, 2022)
Happiness is the ontological state of human nature by which it is defined as a being endowed with reason, will and feeling. Anthropological analysis, whether it is carried out from a theological perspective or from a philosophical perspective, places man in a continuous ascent towards happiness. Thus, the question can be asked: which of the two ethical systems can define the human person as the possessor of morality and happiness, and what are their limits?